2018
DOI: 10.1158/0008-5472.can-17-1492
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Epigenomic Signatures in Ovarian Cancer Associated with Resensitization to Platinum Drugs

Abstract: DNA methylation aberrations have been implicated in acquired resistance to platinum drugs in ovarian cancer. In this study, we elucidated an epigenetic signature associated with platinum drug resensitization that may offer utility in predicting the outcomes of patients who are coadministered a DNA methyltransferase inhibitor. The ovarian cancer specimens we analyzed were derived from a recent clinical trial that compared the responses of patients with recurrent platinum-resistant ovarian cancer who received ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 52 publications
3
77
0
Order By: Relevance
“…The Tukey test for multiple comparisons correction was used to analyze the significance among different groups in biological assays, unless otherwise stated. For in vivo experiments, ANOVA/ Mann-Whitney tests (GraphPad) were used to determine statistical significance, as described (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Tukey test for multiple comparisons correction was used to analyze the significance among different groups in biological assays, unless otherwise stated. For in vivo experiments, ANOVA/ Mann-Whitney tests (GraphPad) were used to determine statistical significance, as described (23).…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous reports demonstrating a functional role for DNMT1 in DNA repair (DDR; refs. 20,21) and our previous studies demonstrating DNMTis ability to resensitize tumors to primary therapies (22,23), we hypothesized that combining a DNMTi with PARPi would sensitize PARPi-resistant ovarian cancer to PARPi therapy, regardless of BRCA status. In support of our hypothesis, it was recently demonstrated that DNMTi-PARPi combination induced PARPi sensitization in leukemia and breast cancer models (24), further suggesting that such a combination approach would impair BRCA-mediated DDR, resulting in cytotoxicity in cells harboring intact or mutant BRCA1/2.…”
Section: Introductionmentioning
confidence: 95%
“…Resistance/sensitization Genes Cisplatin resistance OXCT1 [18] , GPCR [19] , TET1 [20] , MLH1 [21][22][23] , HOXA10, HOXA11 [21,24] , NAGA [25] , UCHL1 [26] , BCL2L1 [27] , FANCF [28][29][30] Cisplatin sensitization FANCF [31] , NAGA [25] , CCDC69 [32] , UCHL1 [26] Carboplatin Resistance TMEM88 [33] , DOK2 [34,35] , p57(Kip2) [36] , Plk2 [37] , HERV-K [38] , SFRP5 [39] , SLFN11 [40] , ASS1 [41] ASS1: argininosuccinate synthase 1; BCL2L1: BCL2 like 1; CCDC69: coiled-coil domain containing 69; DOK2: docking protein 2; FANCF: fanconi anemia complementation group F; GPCR: protein coupled receptor; HOXA: homeobox A cluster; HERV-K: for HERV-K: human endogenous retrovirus type K; MLH1: mutL homolog 1; NAGA: N-acetylgalactosaminidase; OXCT1: 3-oxoacid CoA-transferase 1; Plk2: polo like kinase 2; SFRP5: secreted frizzled-related protein 5; SLFN11: schlafen family member 11; TET1: tet methylcytosine dioxygenase 1; TMEM88: transmembrane protein 88; UCHL1: ubiquitin C-terminal hydrolase L1 β-catenin independent (non-canonical) pathways. Wnt proteins bind to receptors of the Frizzled and the low-density lipoprotein receptor-related protein families on the cell surface.…”
Section: Table 2 Epigenetically Modifiable Genes Relevant To Ovarianmentioning
confidence: 99%
“…In this context, less than 30% of HGEOC patients survive more than five years [66]. Major causes are identified in diagnosis at advanced stages (III-IV) when the disease has already spread in the abdomen and has acquired or intrinsic resistance to therapy, features that have been linked to CSC and cell plasticity [59,67].…”
Section: Epigenetic Modulators: Hitting the Leitmotiv Across Differenmentioning
confidence: 99%
“…The DNA methylation status may be interpreted as a tumor fingerprint, resembling the traits of the cell of origin. This could be exploited as a useful clinical tool to (i) identify metastasis of uncertain primary tumor, (ii) to refine the molecular classification of tumors, or (iii) to select patients who could benefit from a specific targeted therapy [64,67,73].…”
Section: Dna Methylation: Implication and Inhibitionmentioning
confidence: 99%